DESAIN DAN PROTOTIPE SISTEM INVENTORI BARANG BERBASIS WEBSITE PADA JASA WARNA GYPSUM - Eviana Hartanti; Muhammad Arifin; R. Rhoedy Setiawan (Universitas Serang Raya, 2025)
This paper presents the design and prototype of a web-based inventory system specifically designed for Jasa Warna Gypsum, a retail business engaged in building materials. The main objective of this study is to address the inefficiencies in manual inventory management, which often leads to inaccurate stock data and delays in decision making. This study focuses on creating an easy-to-use UI/UX design that allows for real-time stock monitoring and management. The system design includes key features such as a real-time dashboard, WhatsApp notifications, and simplified stock tracking functionality to optimize inventory control. The research methodology involves a thorough analysis of the existing manual process, gathering user requirements through interviews and observations, and subsequent prototype design based on the identified needs. The UI/UX design was tested through user experience trials, which showed that the proposed system significantly improves efficiency in managing inventory, reduces time for input and output of stock, and minimizes human errors. Although this study was limited to the design and prototype stages, the results indicate that a full implementation of the system has the potential to solve the existing challenges in inventory management at Toko Jasa Warna Gypsum. This study concludes that the web-based inventory system design successfully meets its objectives and can serve as a baseline model for further development. Future research is recommended to focus on the full implementation and integration of the system in a real-world environment, expanding its capabilities for wider use in similar retail environments. The proposed system also has potential for further optimization, such as mobile integration and advanced reporting features. Keywords: inventory system, web-based, UI/UX design, inventory management, real-time monitoring